Systolic and Diastolic Cardiac Functions in Juvenile Spondyloarthropathies. Issue 1 (January 2022) - Yildiz, Mehmet; Dedeoglu, Reyhan; Akdeniz, Beste; Adrovic, Amra; Haslak, Fatih; Karagozlu, Fatih; Koker, Oya; Ulug, Nujin; Sahin, Sezgin; Barut, Kenan; Oztunc, Funda; Kasapcopur, Ozgur
Abstract : Background/Objective: Juvenile spondyloarthropathies (JSpAs) are a group of inflammatory diseases characterized by asymmetric peripheral arthritis (especially in lower extremities), axial skeleton involvement, and enthesitis. Although cardiovascular findings of inflammatory diseases such as juvenile systemic lupus erythematosus (SLE) and juvenile scleroderma (SD) are well documented, there are only a few studies assessing the cardiovascular consequences of JSpA in the literature. Methods: Forty patients with JSpA and 20 healthy controls were included into this cross-sectional study. Cardiac functions of the participants were evaluated by conventional echocardiography and pulse-wave (PW) tissue Doppler. Results: The patients with JSpA had higher mitral lateral S ( p = 0.005) and E' wave ( p < 0.001), tricuspid A' wave ( p = 0.03), ejection fraction ( p = 0.03) and shortening fraction ( p = 0.01) than the control patients. In contrast, the patients with JSpA had lower left ventricle MPI ( p = 0.01) and the ratio of tricuspid E'/A' waves ( p = 0.05). Patients with enthesitis detected on magnetic resonance imaging had lower ejection fraction ( p = 0.05), the ratio of E/A waves ( p = 0.03) and had higher Mitral lateral A' wave ( p = 0.01) than those without. There was a significant inverse correlation between the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and PW transmitral A velocity ( r = −0.256, p = 0.03), the BASDAI score and tricuspid annular plane systolic excursion ( r = −0.301, p = 0.04), the BASDAI score and the ratio of E/E' waves ( r = −0.276, p = 0.02), and the Juvenile Spondyloarthritis Disease Activity Index and PW transmitral A velocity ( r = −0.246, p = 0.04). Conclusions: In this study, we report the possible early signs of RV diastolic dysfunction and possible association between magnetic resonance imaging–confirmed enthesitis and lower LV systolic functions. Early identification of cardiac dysfunctions can help with prevention of long-term cardiovascular complications. Abstract : Supplemental digital content is available in the text.